Pengaruh Economic Value Added, Market Value Added, Dan Price Earning Ratio Terhadap Return Saham Pada PT. Telkom Indonesia Tbk - Ahsanul Hadi Amin; Lukmanul Hakim (Shafin: Sharia Finance and Accounting Journal, 2022)
The purpose of this study is to test whether there is an effect of Economic Value Added, Market Value Added, and Price Earning Ratio on stock returns at PT. Telkom Indonesia Tbk either partially or simultaneously. In the results of the classical assumption test, there are symptoms of autocorrelation and heteroscedasticity, so the researcher decided to transform the data using the Cochrane Orcutt method. This study uses a quantitative approach with the type of associative research. The sample used is the quarterly financial statements of PT. Telkom Indonesia Tbk for the 2009-2020 period as many as 48 financial reports. The results of this study indicate that the Economic Value Added, Market Value Added, and Price Earning Ratio have no significant effect on stock returns at PT. Telkom Indonesia, because the value of fcount < ftable is 0.476 < 2.82 with a significance value of > 0.05. Economic Value Added has no significant effect on stock returns at PT. Telkom Indonesia, because the value of tcount < ttable is -0.014 < 2.014 with a significance value of > 0.05. Market Value Added has no significant effect on stock returns at PT. Telkom Indonesia, because the value of tcount < ttable is 1.129 < 2.014 with a significance value of > 0.05. Price Earning Ratio has no significant effect on stock returns at PT. Telkom Indonesia because the value of tcount < ttable is -0.798 < 2.014 with a significance value of > 0.05.